EFEKTIVITAS AROMATERAPI LAVENDER DALAM MENGURANGI RASA NYERI IBU POSTPARTUM: TINJAUAN LITERATUR - Grahardika Andani, Elga Caecaria; Ganisia, Ainun; Fathiyyah, Nurul (Rena Cipta Mandiri, 2026)
The postpartum period is frequently associated with pain caused by uterine contractions, perineal trauma, or cesarean wounds, which may limit mobilization and negatively affect physical and psychological recovery. Non-pharmacological approaches such as Lavandula angustifolia aromatherapy are increasingly explored because they are simple, safe, and have minimal side effects. This narrative literature review analyzed studies published between 2020 and 2025 retrieved from Google Scholar focusing on lavender aromatherapy interventions for postpartum mothers. Evidence indicates that active compounds including linalool and linalyl acetate provide sedative and analgesic effects by stimulating the limbic system and enhancing endorphin release. Inhaled lavender aroma was consistently associated with reduced pain intensity in mothers experiencing perineal pain and post-cesarean discomfort. Overall, lavender aromatherapy appears to be an effective complementary therapy that promotes relaxation, improves comfort, supports emotional well-being, and facilitates a smoother postpartum recovery process for mothers.